HUBUNGAN ANTARA KELEKATAN ORANGTUA DENGAN REGULASI EMOSI REMAJA PONDOK PESANTREN AGRO “NUUR EL-FALAH” SALATIGA - Rahma Ajeng Pawulan; Lobby Loekmono; Sapto Irawan (Universitas Negeri Medan, 2018)
This study aims to determine the sicnificance of the relationship between parent attachment and emotional regulation of adolescents Agro